Energy efficiency analysis of broadcast and communication converged network - Cheng-jie SHEN; Yun RUI; Guo-ming QIAN; Fei HUANG; Ming-qi LI (Tongxin xuebao)
A novel system model and energy efficiency analysis method were studied to solve the problem of the per-formance analysis of broadcast and communication converged network. From the perspective of the user request, the business could be classified as the popular part and the non-popular part. Based on the random spatial network model, cellular base stations and users were modeled as two independent spatial Poisson point processes (PPP), while the broad-cast tower was assumed to locate in the center of service regions. By further exploiting the coverage of broadcast network and the outage probability of cellular network, the closed-form expression of the converged network energy efficiency (EE) was derived, and the impact of popular business probability to the energy efficiency was discussed. Simulation re-sults show that assuming the mentioned converged system model and the general density of BS and user, the energy effi-ciency of converged network would be significantly improved compared to pure cellular network when the probability of popular businesses is more than 5%. The novel model and energy efficiency analysis method provide the foundation for the study of the overall performance of the converged network.